ARTISTIC REFLECTION OF SOCIO-POLITICAL REALITIES THROUGH SYMBOLS IN AZERBAIJANI AND BRITISH DRAMATURGY (KONFERENSIYA, 2026)
This article discusses common creative principles in Azerbaijani and British literature at the beginning of the 20th century. It notes that some Azerbaijani and British playwrights wrote about the same themes and problems and held the same artistic and philosophical views, and that the methods they used to express these ideas were also similar. Thus, when reflecting on the same issues in literature from both nations at that time, playwrights from both countries used almost the same symbols. In other words, the works of certain playwrights have the same symbolic meaning. The article analyses this issue by comparing the works of J. Mammadguluzadeh, H. Javid, U. B. Yeats and D. H. Lawrence.